The Relationship Between Family Support And Motivation To Recover Among Residents At The BNN Rehabilitation Centre In Bengkulu Province In 2025 - Sari, Lola Anma; Susanti , Meri Epriana; Marlianto, Nuche (Utami Publisher, 2026)
According to UNODC data reports in 2023, the number of drug users worldwide is around 296 million people, equivalent to 5.8% of the world's population aged 15-64 years. The purpose of this study is to examine the relationship between family support and motivation to recover among residents at the Bengkulu Province BNN Rehabilitation Centre in 2025. The research method used was analytical observational research with a cross-sectional approach. The sampling technique used total sampling with a sample size of 45 drug residents at the Bengkulu Province BNN Rehabilitation Centre. The results of the univariate analysis showed that most of the respondents (66.7%) had supportive families, and most of the respondents (73.3%) had high motivation to recover. The results of the bivariate analysis showed a relationship between family support and motivation to recover among residents (p=0.000). There is a relationship between family support and motivation to recover among residents at the Bengkulu Province BNN Rehabilitation Centre in 2025. The researcher recommends that respondents remain focused on recovery and enhance their motivation to recover, and that the BNN Provincial Rehabilitation Centre in Bengkulu adopt an approach towards residents to continuously provide encouragement and motivation in their rehabilitation process.